Factors that influence public participation in local authority's environmental activities / Nurfadliah Shahirah Mohd Nordin and Nurul Auni Zulkomain - Mohd Nordin, Nurfadliah Shahirah; Zulkomain, Nurul Auni (2018)
According to the Gauthier et.al, (2011), the author defined that public participation known as the continuous which is the two-way communication process that involves promoting full public understanding of the processes and mechanisms through the environmental problems and needs were investigated and solved by the responsible agency. This to ensure that public keep informed about the status and progress, implications of project, plan, and program and policy formulation and also the evaluation activities.